1997
DOI: 10.2141/jpsa.34.9
|View full text |Cite
|
Sign up to set email alerts
|

DNA Fingerprinting Analysis of Native and Red Jungle Fowls in Fiji and Western Samoa.

Abstract: In the present study, genomic DNA was prepared from dried chicken blood sample and subsequently used for analyzing DNA fingerprinting (DFP) of native and Red jungle fowl in the South Pacific Islands.These chicken genomic DNAs were sufficient in quantity and purity for multiple DFP analyses, and chicken blood could be stored for up to 3 months without physical degradation under dry condition. The DFP analyses were carried out by individual and population DFP. Similarities of DFP patterns and genetic distances a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…The band sharing values between the domestic chickens, on the one hand, and the species G. gallus, G. sonnerati, G. lafayettei, and G. varius, on the other hand, were respectively 0.272, 0.221, 0.233 and 0.089. In a subsequent study using minisatellites, the same Japanese researchers [59] clearly demonstrated a substantial contribution of the geographical component to the similarity degree between G. gallus, local domestics and their hybrids bred in Fiji and Western Samoa. The specimens of an RJF population kept at the Kagoshima University were also used in the investigation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The band sharing values between the domestic chickens, on the one hand, and the species G. gallus, G. sonnerati, G. lafayettei, and G. varius, on the other hand, were respectively 0.272, 0.221, 0.233 and 0.089. In a subsequent study using minisatellites, the same Japanese researchers [59] clearly demonstrated a substantial contribution of the geographical component to the similarity degree between G. gallus, local domestics and their hybrids bred in Fiji and Western Samoa. The specimens of an RJF population kept at the Kagoshima University were also used in the investigation.…”
Section: Discussionmentioning
confidence: 91%
“…Enough convincing evidence has also established a similarity for biochemical and molecular markers between indigenous chicken breeds and G. gallus populations inhabiting the same geographical region [22,23,58]. In other cases, especially with the usage of molecular markers [45,59,60], a clear and repeated picture has not yet been achieved.…”
Section: Discussionmentioning
confidence: 99%